Leveraging the Tracking Operations and Outcomes for Plastic Surgeons Database for Plastic Surgery Research: A "How-To" Guide. Issue 5 (November 2021) - Valente, Denis Souto; Kaye, Alison E.; Simmons, Christopher J.; Zanella, Rafaela K.; Pannucci, Christopher J.
Abstract : Summary: The Plastic Surgeries Registry Network supported by the American Society of Plastic Surgeons (ASPS) and the Plastic Surgery Foundation offers a variety of options for procedural data and outcomes assessment and research. The Tracking Operations and Outcomes for Plastic Surgeons (TOPS) database is a registry created for and used by active members of ASPS to monitor all types of procedural outcomes. It functions as a way for individual or group practices to follow surgical outcomes and constitutes a huge research registry available to ASPS members to access for registry-based projects. The TOPS registry was launched in 2002 and has undergone several iterations and improvements over the years and now includes more than 1 million procedure records. Although ASPS member surgeons have proven valuable assets in contributing their data to the TOPS registry, fewer have leveraged the database for registry-based research. This article overviews the authors' experience using the TOPS registry for a database research project to demonstrate the process, usefulness, and accessibility of TOPS data for ASPS member surgeons to conduct registry-based research. This article pairs with the report of the authors' TOPS registry investigation related to 30-day adverse events associated with incision location for augmentation mammaplasty.